Effectiveness of Digital Pedagogy in Higher Mathematics Education - Dhakal, Bed Prasad (Journal of Development and Administrative Studies, 2018)
The use of digital technology in education has revolutionized traditional teaching methods, particularly in mathematics education. This study aims to examine the effectiveness of digital pedagogy in higher mathematics education. The research question focuses on analyzing the effectiveness of digital pedagogy on students' APOS-based learning achievements in higher mathematics. The study used a quantitative research approach, employing a critical Action Research design with pre-and post-test measures to assess the effectiveness of digital pedagogy. The study participants were 126 third-semester students taking a course "Differential Geometry". The used tools are the DP model and mathematics achievement test (MAT). Based on the analysis of data, it is found that DP is effective to enhance APOS-based students learning. So, the study concludes that Digital Pedagogy in higher mathematics education provides insights into how educators can leverage technology to enhance student learning outcomes.